Kontaminasi Telur Cacing pada Sayur dan Upaya Pencegahannya - Hebert Adrianto (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
Helminth infections are the most common infections in developing countries and still need to be eradicated. Fresh vegetables can be the source for transmission of helminth egg to humans. The aims of this paper are to identify the types of helminth egg which found in vegetables and prevention efforts according to the helminth life cycle. A literature review was arranged by review of 4 articles Indonesian research journal, 22 articles non Indonesia research journal, WHO website, and textbooks relevant to the study topic. The paper describes list of helminth eggs in vegetables, environmental, behaviors, and host-related helminth analyzes in vegetables, and prevention efforts based life cycle of helminthes. The study found that helminth eggs in vegetables were not only Soil Transmitted Helminth (STH) Nematode such as Ascaris lumbricoides, Trichuris trichiura, Necator americanus, Ancylostoma duodenale, and Strongyloides stercoralis, but also another nematode (Trichostrongylus, Toxocara, Trichocephal, and Enterobius vermicularis), cestoda groups (Taenia spp., Hymenolepis nana, and H. diminuta), Trematode groups (Heterophyes heterophyes, Clonorchis sinensis, Fasciola, and Dicrocoelium dendriticum). Each helminthes species have a different life cycle and intermediate host. Our prevention efforts to avoid infection risk require cooperation across programs, sectors, and community and should consider the helminth life cycles.